The impact of overweight and obese on quality of life among Malay breast and gynecology cancer survivors from two hospital in Kuala Lumpur - Mohd Razif, S; Nadzirah, HZ; Suhaina, S; Yulianty, A; Ibtisqm, MN; Zabedah, O; Fuad, I (2016)
Overweight and obesity are factors that contribute to increase risk of non-communicable diseases and cancer recurrence. Therefore, a study was conducted to identify the effects of body mass index (BMI) towards quality of life among breast (BrCa) and grnecologr (GynCa) cancer survivors. A cross-sectional study using purposive sampiing method was conducted among 101 Malay BrCa(63.4oh) and GynCa(36.6%), was at stage II cancer (41.2%) and recruited from Outpatient Clinics of Hospital Kuala Lumpur and Hospital Canselor Tuanku Muhriz. Their mean age were 51.1 t 8.3 years and had completed treatment for 4.2 + 3.4 years. Physical activity level was assessed using IPAQ POO2). A general questionnaire measuring quality of life (QoL) for cancer EORTC QLQ C3O and specific questionnaires related to types of cancers (QLQ BR 23, QLQ OV23, QLQ EN24, QLQ CX24) were used. Results showed that mean body weight and mean BMI of subjects for both types of cancers were 66.2 t 15.6 kgand 28.0 I 5.4kglrn2 (p>0.05) respectively. BMI status indicated that more than half of subjects were in the category of overweight (31.4%) and obese (34.3%). Similar sitting time (p>0.05) ald low level of physical activity (p>0.05) were observed among BrCa (7 4.6ok) and GynCa (7 8.8%) subjects. The main barrier in performing physical activity amongst both types of cancer subjects were fatigue due to cancer treatments. Global health QoL (QLQ 30) score showed BrCa and GynCa subjects had good mean score (TOIIOO). Subjects experienced similar functional and symptom problems for all scales of QLQ C-30 (p>0.05). No significant difference was seen in all categories of BMI for all QoL scales. In conclusion cancer survivors of all categories of BMI had similar effects on the QoL scales. He4ce, the development of educationa-l module can be adopted for all categories of BMI with focus on Malay socio-culture.